2016
DOI: 10.1177/1535370216648806
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering signaling networks in osteosarcoma pathobiology

Abstract: Osteosarcoma is the most frequent type of primary bone tumors among children and adolescents. During the past years, little progress has been made regarding prognosis of osteosarcoma patients, especially for those with metastatic disease. Genomic instability and gene alterations are common, but current data do not reveal a consistent and repeatable pattern of osteosarcoma development, thus paralleling the tumor's high heterogeneity. Critical signal transduction pathways have been implicated in osteosarcoma pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 88 publications
(152 reference statements)
1
37
0
Order By: Relevance
“…The functions of most of these molecules and pathways in bone development and disease have been studied in detail [73, 92-100]. Results from these completed trials, as well as from studies evaluating other types of treatments such as immunotherapy, have been reviewed recently and will not be described here [9, 101-105]. In general, the findings from these targeted therapy trials have been unsatisfactory.…”
Section: Driver-dependent Genetic Vulnerabilities As Targets Of Osmentioning
confidence: 99%
“…The functions of most of these molecules and pathways in bone development and disease have been studied in detail [73, 92-100]. Results from these completed trials, as well as from studies evaluating other types of treatments such as immunotherapy, have been reviewed recently and will not be described here [9, 101-105]. In general, the findings from these targeted therapy trials have been unsatisfactory.…”
Section: Driver-dependent Genetic Vulnerabilities As Targets Of Osmentioning
confidence: 99%
“…The phosphatidylinositol 3-kinase PI3K/Akt pathway is considered one of the most critical pathways in osteosarcoma pathogenesis regulating osteosarcoma cell proliferation, invasion, metastasis, and drug sensitivity or resistance [84,85].…”
Section: Lncrnas and Signal Transduction Pathways In Osteosarcomamentioning
confidence: 99%
“…MALAT-1 also acts through the PI3K/Akt pathway to promote osteosarcoma cell proliferation, migration, invasion, and pulmonary metastasis. Furthermore, MALAT-1 knockdown or siRNA interference experiments, carried out by Dong et al and Cai et al, respectively, showed that MALAT1 inhibition suppressed osteosarcoma cell proliferation and metastasis via the PI3K/Akt and RhoA/ROCK signaling pathways by modulating the expression of MMP-9 metalloproteinase [85,87,88]. MALAT-1 is highly expressed in osteosarcoma tissue samples and is correlated with metastatic dissemination and advanced clinical stage [142,143].…”
Section: Lncrnas and Invasion/metastasis In Osteosarcomamentioning
confidence: 99%
“…3 Molecular alterations in coding RNA-or noncoding RNA (ncRNA)-mediated key signalling pathways are pivotal for tumour progression in osteosarcoma pathogenesis, including cell growth, metastasis, and invasion. 4,5 As such, recognizing the target molecules may provide new diagnosis and treatment regimens for osteosarcoma cases.…”
Section: Introductionmentioning
confidence: 99%